The Hajj and Europe in the Age of Empire (2017)
"Killed the pilgrims and persecuted them with all kinds of cruelties": Portuguese Estado da India's encounters with the hajj in the sixteenth century / Mahmood Kooria – "The infidel piloting the true believer": Thomas Cook and the business of the colonial hajj / Michael Christopher Low – British colonial knowledge and the hajj in the Age of Empire / John Slight – French policy and the hajj in late-nineteenth-century Algeria: Governor Cambon's reform attempts and Jules Gervais-Courtellemont's pilgrimage to Mecca / Aldo d'aAostini – Heinrich Freiherr von Maltzan's "My pilgrimage to Mecca": a critical investigation / Ulrike Freitag – Polish connections to the hajj in the nineteenth century: mystical and imaginary travels to Mecca and the Polish cultural tradition / Boguslaw R. Zagorski – On his donkey to the mountain of 'Arafat: Dr. Van der Hoog and his hajj journey to Mecca / Umar Ryad – "I have to disguise myself": orientalism, Gyula Germanus, and pilgrimage as cultural capital, 1935-1965 / Adam <estyan – Franco's North African pilgrims after WWII: the hajj through the eyes of a Spanish colonial officer / Josep Lluis Mateo Dieste.